Credit rating and pricing: Poles apart - Andreas Blöchlinger (Journal of Risk and Financial Management, 2018)
Corporate credit ratings remove the information asymmetry between lenders and borrowers to find an equilibrium price. Structured finance ratings, however, are informationally insufficient because the systematic risk of equally rated assets can vary substantially. As I demonstrate in a Monte Carlo analysis, highly-rated structured finance bonds can exhibit far higher non-linear systematic risks than lowly-rated corporate bonds. I value credit instruments under a four-moment CAPM, between and within some markets there is no one-to-one relation between expected loss (rating) and credit spread (pricing). The linear CAPM beta is insufficient, buyers and sellers need also the same information on non-linear risk to have an equilibrium.
Keywords: 330; asset backed security (ABS); contingent convertible bond (CoCo); standard risk aversion; capital asset pricing model (CAPM); UBS crisis